Outcome of patients with HTLV-1-associated adult T-cell leukemia/lymphoma after SCT: a retrospective study by the EBMT LWP - Bazarbachi, Ali; Cwynarski, K.; Boumendil, A.; Finel, H.; Fields, P.; Raj, K.; Nagler, A.; Mohty, M.; Sureda, A.; Dreger, Peter; Hermine, O. (Bone marrow transplantation, 2014)
Adult T-cell leukemia/lymphoma (ATL) carries a dismal prognosis. Experience with allo-SCT for ATL appears encouraging but is limited to Japanese series. This retrospective analysis of the EBMT registry revealed 21 HTLV-I seropositive ATL including 7 acute and 12 lymphoma subtypes. Four patients received auto-SCT and rapidly died from ATL. Out of 17 allo-SCT (4 myeloablative, 13 reduced intensity), 6 are still alive (4 were in CR1 at SCT). Eleven patients died within 2 years, eight from relapse/progression and three from transplant toxicity. Six of seven informative patients who lived >12 months had chronic GVHD. Overall these results indicate that allo-SCT but not auto-SCT may salvage a subset of ATL patients, supporting the existence of graft vs ATL effect also in non-Japanese patients.